355 Fetal Growth is Associated with Altered Expression of Imprinted Genes in the Placenta. (October 2012) - Piyasena, C; Khulan, B; Menon, G; Drake, AJ
Abstract : Background and Aims: Both low and high birthweight is associated with adverse health outcomes throughout life. Altered expression of imprinted genes which regulate fetal and placental growth may be one mechanism linking the environment and later disease risk. We have studied the expression of candidate imprinted genes in placenta with respect to anthropometric parameters at birth. Methods: 58 term placentas (27 male) were obtained from the Edinburgh Reproductive Tissue BioBank. Pregnancies complicated by congenital abnormalities or diabetes were excluded. Gene expression was analysed using real-time PCR. Results: Median birthweight was 3900g (interquartile range: 2949–4340g). Insulin-like growth factor 2 (IGF2) mRNA levels correlated positively with standard deviation scores for birthweight (Spearman's rho=0.335, p =0.005), head circumference (Spearman's rho=0.424, p =0.001) and length (Spearman's rho=0.259, p =0.041). Growth factor receptor-bound protein 10 (GRB10) mRNA levels correlated negatively with birthweight standard deviation score (Spearman's rho= –0.221, p =0.048). The expression of two other imprinted genes, PHLDA2 and ZIM2 showed no relation to size at birth. Conclusion: Both IGF2 and GRB10 are imprinted in the placenta and impact on fetal and placental growth. IGF2 is paternally imprinted and increased expression is implicated in overgrowth disorders; in contrast, GRB10 is maternally imprinted in trophoblasts and disruption in mice leads to overgrowth. Additionally, GRB10 has recently been identified as having a role in insulin signaling. As genomic imprinting is under epigenetic regulation, these targets are strong candidates for exploration of environmentally influenced non-Mendelian effects on fetal size and developmental programming.